Should the tenant of land possess the property in the improvements made by him? - Heron, Denis Caulfield (Statistical and Social Inquiry Society of Ireland, 1852)
I wish to discuss the question which I have prefixed to this paper for the consideration of the society, without direct reference to the existing Tenant Right of Ulster, or to the reforms in the law of real property which are now demanded. I merely wish to ascertain whether, as a pure question of natural law, the property in improvements made by the tenant, should not be vested in him alone. It is one of the principal advantages to be gained from the study of sociology, and from the institution of a society such as this, that questions formerly termed political are brought within the domain of philosophical enquiry, and subjected to the same processes by which such great results have been obtained in the physical sciences.
Read May 17th 1852
Keywords: Tenant rights; Farm improvements; 314.15